Kinetics and persistence of cellular and humoral immune responses to SARS‐CoV‐2 vaccine in healthcare workers with or without prior COVID‐19. Issue 4 (18th January 2022) - Chivu‐Economescu, Mihaela; Bleotu, Coralia; Grancea, Camelia; Chiriac, Daniela; Botezatu, Anca; Iancu, Iulia V.; Pitica, Ioana; Necula, Laura G.; Neagu, Ana; Matei, Lilia; Dragu, Denisa; Sultana, Camelia; et al.
Abstract: SARS‐CoV‐2 vaccines are highly efficient against severe forms of the disease, hospitalization and death. Nevertheless, insufficient protection against several circulating viral variants might suggest waning immunity and the need for an additional vaccine dose. We conducted a longitudinal study on the kinetics and persistence of immune responses in healthcare workers vaccinated with two doses of BNT162b2 mRNA vaccine with or without prior SARS‐CoV‐2 infection. No new infections were diagnosed during follow‐up. At 6 months, post‐vaccination or post‐infection, despite a downward trend in the level of anti‐S IgG antibodies, the neutralizing activity does not decrease significantly, remaining higher than 75% (85.14% for subjects with natural infection, 88.82% for vaccinated after prior infection and 78.37% for vaccinated only). In a live‐virus neutralization assay, the highest neutralization titres were present at baseline and at 6 months follow‐up in persons vaccinated after prior infection. Anti‐S IgA levels showed a significant descending trend in vaccinated subjects ( p  < 0.05) after 14 weeks. Cellular immune responses are present even in vaccinated participants with declining antibody levels (index ratio 1.1–3) or low neutralizing activity (30%–40%) at 6 months, although with lower T‐cell stimulation index ( p  = 0.046) and IFN‐ γ secretion ( p  = 0.0007) compared to those with preserved humoral responses.